Characterisation of the structure and thermophysical properties of solid electroslag remelting slags. Issue 12 (12th August 2016) - Plotkowski, A.; deBarbadillo, J.; Krane, M. J. M.
Abstract : The solid structure and thermophysical properties of three electroslag remelting (ESR) slags were characterised. Samples from ESR trials performed by Special Metals Corporation in Burnaugh, KY, were compared to samples solidified in a vacuum induction melter. The microstructures were characterised using a combination of optical and electron microscopy, X-ray diffraction, energy-dispersive spectroscopy and a serial sectioning technique to quantify porosity. The thermophysical properties were measured using differential scanning calorimetry and laser flash diffusivity testing at Thermophysical Property Measurement Laboratory, Inc. in West Lafayette, IN. The two processing routes were found to produce similar phase fractions, but resulted in different properties as a function of phase morphology and porosity content. These results suggest that future modelling and property measurement efforts must account for both the structure and composition of the slags.